Metode Dakwah Tuan Imam dalam Membina Kehidupan Sosial Jemaah di Kampung Kasih Sayang Matfa Indonesia di Kabupaten Langkat - Layalia Husna Saragih (Prodi Perpustakaan dan Sains Informasi, 2023)
This journal reviews the Da'wah Method of Tuan Imam in Fostering the Social Life of the Congregation in Kampung Kasih Sayang Matfa Indonesia in Langkat Regency. Specifically, this research was made to find and analyze: the forms of methods used by Tuan Imam in fostering the social life of his congregation, what kind of social concepts he used and what kind of obstacles and support he faced in fostering the social life of the congregation as a leader in Kampung Kasih Sayang Matfa Indonesia. The approach used is qualitative research in order to get an in-depth description of the data. The data in this study were obtained through interviews, observation and documentation. In this study, the informants were Tuan Imam as the main informant and the congregation as supporting informants. With non-participant observation. The results of this study indicate that there are three da'wah methods used by Tuan Imam in preaching, namely bil-hikmah, mauidzah hasannah and qudwah hasanah/qudwah hasannah, Tuan Imam also uses two social concepts in fostering the social life of the congregation by: social structure and functional integrity. The inhibiting and supporting factors are factors that come from the congregation itself and support from the family and the congregation itself.